2022
DOI: 10.1093/eurheartj/ehac544.1597
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of significant coronary artery disease in patients undergoing transcatheter aortic valve implantation: a systematic review and meta-analysis

Abstract: Background The prevalence of coronary artery disease (CAD) in patients with severe aortic valve stenosis undergoing transcatheter aortic valve implantation (TAVI) is high. However, the importance of a percutaneous coronary intervention (PCI) prior to TAVI has been matter of debate. Importantly, patients undergoing TAVI are characterized by high age often accompanied by highly calcified coronary arteries, increasing the risk of severe periprocedural complications. Moreover, patients with a sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The present study is one of the largest analyses 33 with the longest follow‐up time and the only one so far, evaluating coPCI in TAVI patients according to the VARC‐3 endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is one of the largest analyses 33 with the longest follow‐up time and the only one so far, evaluating coPCI in TAVI patients according to the VARC‐3 endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Current international guidelines recommend angiographic evaluation for patients with CAD exhibiting >70% stenosis in the proximal segment (or >50% stenosis in the left main artery) with planned PCI based on angiography findings (class IIa, class C) [4]. Several studies on the treatment of patients with aortic stenosis and CAD [5][6][7] have indicated that PCI before or during TAVR does not significantly increase all-cause mortality and cardiovascular mortality compared to TAVR alone. It, however, remains uncertain whether the timing of PCI plus TAVR offers any additional clinical benefits for patients with severe aortic stenosis and CAD.…”
Section: Introductionmentioning
confidence: 99%